Spin-resolved imaging of atomic-scale helimagnetism in mono- and bilayer NiI 2 - Mao-Peng Miao; Nanshu Liu; Wen-Hao Zhang; Jian-Wang Zhou; Dao-Bo Wang; Cong Wang; Wei Ji; Ying-Shuang Fu (Proceedings of the National Academy of Sciences, 2025)
Noncollinear magnetic orders in monolayer van der Waals magnets are crucial for probing delicate magnetic interactions under minimal spatial constraints and advancing miniaturized spintronic devices. Despite their significance, achieving atomic-scale identification remains challenging. In this study, we utilized spin-polarized scanning tunneling microscopy and density functional theory calculations to identify spin-spiral orders in mono- and bilayer NiI 2 , grown on graphene-covered SiC(0001) substrates. We found two distinct spin-spiral states with Q vectors aligning and deviating by 7° from the lattice direction, exhibiting periodicities of 4.54 and 5.01 times the lattice constant, respectively. These findings contrast with bulk properties and align closely with our theoretical calculations. Surprisingly, the nonmultiples of spin spirals within finite-sized magnetic domains induce net magnetic moments, facilitating collective spin switching behavior under magnetic fields. Our research reveals intrinsic noncollinear magnetism at the monolayer limit with atomic-scale resolution, paving the way for exploring spin phenomena.